1986
DOI: 10.1002/ajmg.1320230114
|View full text |Cite
|
Sign up to set email alerts
|

Speech disturbances (cluttering) in mildly impaired males with the Martin‐Bell/fragile X syndrome

Abstract: The language characteristics of fra(X) males (n = 10) with an IQ greater than or equal to 70 were evaluated. Language testing demonstrated relatively stronger receptive vocabulary skills compared to weak auditory memory and processing skills. A characteristic speech and language disturbance, cluttering, was present in 9 of the 10 study patients. Their speech was characterized by a fast and fluctuating rate of speech, and repetitions of sounds, words or phrases. Other aspects of cluttering including attentional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
1
3

Year Published

1986
1986
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 14 publications
(1 reference statement)
4
59
1
3
Order By: Relevance
“…Affected males display an unusual variability is speaking rate that consists of unpredictable shifts from rapid to slower rates [Hanson et al, 1986]. Variability in rate is seen across all levels of IQ [Hanson et al, 1986], but may be more prevalent in adolescents and adults than in boys [Borghgraef, 1987].…”
Section: Speech Productionmentioning
confidence: 99%
“…Affected males display an unusual variability is speaking rate that consists of unpredictable shifts from rapid to slower rates [Hanson et al, 1986]. Variability in rate is seen across all levels of IQ [Hanson et al, 1986], but may be more prevalent in adolescents and adults than in boys [Borghgraef, 1987].…”
Section: Speech Productionmentioning
confidence: 99%
“…Acima de 12 e até 34 anos, há número significativo de indivíduos em etapas iniciais da comunicação oral 16 . 15,[18][19][20] . Tais manifestações são caracterizadas como fala com repetições de expressões e/ ou frases, ou ainda, ininterrupta e inapropriada sobre um mesmo assunto, a fim de aumentar o prazo para a elaboração da resposta, na tentativa de encontrar o que deveria vir a seguir, uma palavra ou uma frase, para estabelecer estrutura sintática que permitisse a sustentação do diálogo 20 .…”
Section: Aspectos Da Fala E Da Linguagem Na Síndrome Do X Frágilunclassified
“…Tais manifestações são caracterizadas como fala com repetições de expressões e/ ou frases, ou ainda, ininterrupta e inapropriada sobre um mesmo assunto, a fim de aumentar o prazo para a elaboração da resposta, na tentativa de encontrar o que deveria vir a seguir, uma palavra ou uma frase, para estabelecer estrutura sintática que permitisse a sustentação do diálogo 20 . Ainda é frequente encontrar-se na fala de indiví-duos com SXF, distúrbios sintáticos e inconsistência no quadro fonético-fonológico 16,22,23 , além de dificuldade em sequencializar movimentos; os dois úl-timos itens caracterizam o quadro de apraxia fonoarticulatória em indivíduos com SXF 18,23 . A fala na SXF é ser comumente caracterizada como rápida e disfluente.…”
Section: Aspectos Da Fala E Da Linguagem Na Síndrome Do X Frágilunclassified
“…Spcech-related expressive difficulties have been reported in terms of articulation and sound-sequencing difficulties, poor overall intelligibility, a harsh vocal quality, and a variable, impulsive, and rapid speech rate [Newell et al, 1983;Paul et al, 1984;Hanson et al, 1986;Wolf-Schein et al, 1987;Abbeduto and Hagerman, 1997]. Some of the speech difficulties reported in this population have: been a suggested function of a developmental dyspraxia of speech (i.e., difficulties related to the motor planning involved in speech sound production [Dykens et al, 1994;Abbeduto and Hagerman, 1997].…”
Section: Fragile X Syndromementioning
confidence: 99%
“…Although limited, syntactic usc studies of children with FXS haw suggested delays relative to MA-expectancies; however, receptive morpho-syntactic skills appear to be on par with mental age in school-age and adolescent boys [Paul et al, 1984;Abbeduto et al, 2003]. Fluency-related expressive difficulties have been noted in an increased number of dysfluencies, though it has been suggested that these dysfluencies are fewer than those observed in a stuttering disorder [Newell et al, 1983;Paul et al, 1984;Hanson et al, 1986;Wolf-Schein et al, 1987]. Pragmatics-relatcd expressive language difficulties have been distilled into the fragile X syndrome-specific use of deviant, repetitive, and tangential language that is distinguishable, in terms of an increased frequency, from children with autism and children with mental retarelation not caused by fragile X syndrome [Wolf-Schein et al, 1987;Sudhalter et al, 1990;Belser and Sudhalter, 2001;Sudhalter and Belser, 2001].…”
Section: Fragile X Syndromementioning
confidence: 99%